Take the 2-minute tour ×
TeX - LaTeX Stack Exchange is a question and answer site for users of TeX, LaTeX, ConTeXt, and related typesetting systems. It's 100% free, no registration required.

I have a set of aligned equations that I would like to provide an \implies for down the left hand side. I used this originally:

\begin{align}
    (x-1)^2 &= -1    \\
        x-1 &= \pm i \\
          x &= 1 \pm i
\end{align}

which results in a centred set of equations. Then added the \implies in a left column:

\begin{align}
    &          & (x-1)^2 &= -1    \\
    & \implies &     x-1 &= \pm i \\
    & \implies &       x &= 1 \pm i
\end{align}

However now the entire environment is shifted to the right. Is there a way to keep the original alignment?

share|improve this question
add comment

migrated from stackoverflow.com Aug 9 '11 at 22:20

This question came from our site for professional and enthusiast programmers.

2 Answers

up vote 2 down vote accepted

If you want exactly the same alignment as before, but this time with \implies, this does the trick:

\documentclass{article}
\usepackage{amsmath}
\begin{document}
\begin{align}
  (x-1)^2 &= -1     \\
      x-1 &= \pm i  \\
        x &= 1 \pm i
\end{align}

\begin{alignat}{3}
           && (x-1)^2 &= -1      && \phantom{\implies} \\
  \implies &&     x-1 &= \pm i   && \\
  \implies &&       x &= 1 \pm i &&
\end{alignat}
\end{document}

The idea here is to duplicate the width of \implies on the left with a \phantom{\implies} on the right, thereby evenly spacing the equation/environment again.

Aligned equation with \implies

share|improve this answer
add comment

Removing the first alignment character and adding a few \phantoms should do the trick. Alternatively you can use alignat:

\begin{document}
\begin{align}
    (x-1)^2 &= -1    \\
        x-1 &= \pm i \\
          x &= 1 \pm i
\end{align}

\begin{align}
    \phantom{\implies}    (x-1)^2 &= -1    \\
    \implies\phantom{()^2}    x-1 &= \pm i \\
    \implies\phantom{({}-1)^2}  x &= 1 \pm i
\end{align}

 \begin{alignat}{3}
             && (x-1)^2 &= -1    \\
    \implies &&     x-1 &= \pm i \\
    \implies &&       x &= 1 \pm i
 \end{alignat}
 \end{document}
share|improve this answer
add comment

Your Answer

 
discard

By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.